Assessing Sudanese EFL Secondary School Students’ Syntactic and Semantic Knowledge in Utilizing English Connective- words - Musa Ahmed Hassan, Ammar (Gezira Journal of Educational Sciences and Humanities, 2020)
Writing has been one of the most problematic language skill for the most Sudanese EFL Secondary School students; this is may be due to the fact that effective communication, depends to a large extent on the ability to construct a cohesive and coherent text by knowing how to utilize discourse connectives, which are considered one major linguistic devices of clarifying, identifying interrelationships, and encoding cohesive and coherent discourse. The purpose of this study is to investigate how Sudanese EFL Secondary School students use English discourse connectives appropriately for their communicative needs. The data were taken from EFL Sudanese Secondary School students’ written discourse at Wad Medani Secondary School for Boys in Greater Wad Medani Locality, Gezira State- Sudan. The aim is to analyze how well EFL Sudanese students at Secondary level produce logical connectors in accordance with their semantic cohesive functions they fulfill, and to sensitize Sudanese EFL students at Secondary level to the different types of English discourse connectives in order to write a well-organized  written discourse. In addition, to test how Sudanese EFL Secondary School students understand the functions of the different kinds of connective words, and the meaning relationships signaled by these connective words. The functions of these connectors were classified according to the model of Halliday and Hasan. The model of classification and the quantitative analysis of the study subjects’ data were presented together with the results revealed from grading of a taken sample (n=30).  The findings revealed that Sudanese EFL Secondary School students encounter difficulties in the use of a variety of additive, adversative, temporal, and causal connective words; since their frequencies of incorrect responses is (2180 instances, i.e. 56%), which is more than that of correct responses (1706 instances, i.e. 44%). Thus, the findings of this study would be beneficial and advantageous for both language learners and language teachers. The study recommended that in order to comprehend better discourse connectives syntactic and semantic rules, Sudanese EFL  Secondary School students may need be exposed to a higher degree of English connectives and assigning the students a lot of reading and writing assigments.